2012
DOI: 10.1371/journal.pone.0039503
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Investigating Healthy Lifestyle Interventions Incorporating Goal Setting Strategies for Preventing Excess Gestational Weight Gain

Abstract: BackgroundExcess gestational weight gain (GWG) is an important risk factor for long term obesity in women. However, current interventions aimed at preventing excess GWG appear to have a limited effect. Several studies have highlighted the importance of linking theory with empirical evidence for producing effective interventions for behaviour change. Theorists have demonstrated that goals can be an important source of human motivation and goal setting has shown promise in promoting diet and physical activity be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 57 publications
3
80
1
Order By: Relevance
“…The following supporting strategies are commonly utilized in effective studies: goal setting, regular weight monitoring, use of weight-gain graphs to visualize weight gain, verbal feedback on success toward goals, and self-monitoring of diet and PA through the use of food and/or PA records, pedometers, and food scales. 72 Increases in frequency of contact when failing to meet goals, either through phone contact, postcards, or in person, have been recommended to increase success. It has been suggested that obese women may respond to individualized goal setting more than approaches that include less-personal engagement.…”
Section: Prevention Of Excessive Gestational Weight Gain and Related mentioning
confidence: 99%
See 2 more Smart Citations
“…The following supporting strategies are commonly utilized in effective studies: goal setting, regular weight monitoring, use of weight-gain graphs to visualize weight gain, verbal feedback on success toward goals, and self-monitoring of diet and PA through the use of food and/or PA records, pedometers, and food scales. 72 Increases in frequency of contact when failing to meet goals, either through phone contact, postcards, or in person, have been recommended to increase success. It has been suggested that obese women may respond to individualized goal setting more than approaches that include less-personal engagement.…”
Section: Prevention Of Excessive Gestational Weight Gain and Related mentioning
confidence: 99%
“…It has been suggested that obese women may respond to individualized goal setting more than approaches that include less-personal engagement. 72 A randomized controlled trial of 425 pregnant women with a BMI !30 who were randomly assigned to one of two intervention groups or a control group assessed the primary outcome measure of gestational weight gain. 73 Secondary outcome measures of pregnancy complications and delivery and neonatal outcomes were also examined in this study.…”
Section: Prevention Of Excessive Gestational Weight Gain and Related mentioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews have attempted to discern effective BCTs from GWG interventions, with provision of information on the consequences of behaviour to the individual, motivational interviewing, self-monitoring of behaviour, providing rewards contingent on successful behaviour (Hill et al, 2013a), and goal setting (Brown et al, 2012) potentially useful strategies to help women achieve optimal GWG. It is interesting to note that despite the inclusion of 11 BCTs in HIPP (see Skouteris et al, 2015), including BCTs that have previously been found to be effective, efficacy was not established in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The average retention rate across lifestyle intervention studies was $70% in various systematic reviews including intervention RCTs in primary care settings specifically [8][9][10][11]. The intervention attendance rates were not always reported in lifestyle intervention RCTs, although the information is critical for interpreting findings [11].…”
Section: Introductionmentioning
confidence: 99%